ANALISISIS PENENTU MASALAH KETIDAKAMANAN PANGAN JAJANAN ANAK SEKOLAH SERTA ALTERNATIF PROGRAM PENANGGULANGANNYA (Analysis of determinants of street food safety issues and formulate of its eradication program alternatives) - Tanziha, Ikeu; Sumarti, Titik; Indiati, Laksmi; Riyani, Ety; Hastuti, Dwi (-)
The Objectivie of this study was to analyze the determinants of street food safety issues and formulate of its eradicatian program. The study used Survey methods and was conducted from April to August 2012 in Padang and Serang Districts.The The total number of 96 students from Padang District and 90 students from Serang District were selected purposively.The streed food issues data was taken  through focus grroup discussion of stakeholder (teachers, parents of students, vendors, and staff of the relevant agencies) and was analyzed using Interpretative Structure Modelling (ISM). The result showed that there are six determinats of street food safety issues namely: low level of street food vendor moral; a harmful additive still sold freely; coachingandsupervisiontostreet food vendorare stilllow; very low prices of harmful additives; The  government still allowed the production of a harmful additives;  additional ingredient dangerous; supervision on hawker food producers school children is still not a priority program